Peripapillary Microvascular and Structural Parameters in Atrophic Nonarteritic Anterior Ischemic Optic Neuropathy and Their Unaffected Fellow Eyes. Issue 4 (24th December 2022) - Hondur, Gozde; Budakoglu, Ozlem
Abstract : Background: This cross-sectional study aimed to evaluate the peripapillary vessel density (VD), peripapillary retinal nerve fiber layer (RNFL) thickness values of eyes with atrophic nonarteritic anterior ischemic optic neuropathy (NAION), and unaffected fellow eyes. Methods: Peripapillary VDs and RNFL thicknesses in the peripapillary region and 4 sectors (superior, inferior, nasal, and temporal) were evaluated using optical coherence tomography angiography among 19 atrophic NAION eyes, 19 unaffected fellow eyes, and 22 age-matched and sex-matched healthy controls. Results: The NAION eyes had lower peripapillary VD and RNFL thickness values in all areas compared with both the fellow and the healthy control eyes ( P < 0.001 for all). The fellow eyes also demonstrated lower peripapillary VD values ( P = 0.02) despite similar RNFL thickness values ( P = 0.99) in the peripapillary region compared with the age-matched and sex-matched healthy controls. The peripapillary RNFL thickness values significantly correlated with peripapillary VD values in both NAION and fellow eyes. Conclusions: Diminished RNFL thickness and peripapillary VD values were observed in atrophic NAION eyes. In addition, a tendency for a lower peripapillary VD despite similar RNFL thickness values in the fellow eyes may indicate the potential vascular risk factors for NAION.